Moringa oleifera L.: A Potential Plant for Greenhouse Gas Mitigation in Temperate Agriculture Systems - Sofkova-Bobcheva S (Versita)
The earth’s climate is changing because of the increase in greenhouse gas (GHG) concentration, to which livestock is a major contributor. Methane produced from cattle can be reduced by using high quality forages. This study compared the GHG produced from M. oleifera in an artificial ruminant system with two high quality pasture species, ryegrass and white clover. Methane and total gas production were measured using an in vitro batch culture system. A preliminary screening using oven dried M. oleifera planted in field and greenhouse, and a main experiment using six provenances of M. oleifera, a composite sample and M. oleifera leaves from greenhouse was undertaken. Both experiments compared the M. oleifera from different sources with high quality ryegrass and white clover. Real time gas production was recorded for 48 h, total gas production, methane analysed at 12 and 24 h. Short chain fatty acids concentration were also determined at the end of the fermentation. Preliminary results showed that M. oleifera leaves grown in field and greenhouse have lower gas and methane production compared with ryegrass, but similar to white clover. The differences were driven by a high production of propionic and butyric acids. The six M. oleifera provenances also produced less methane than ryegrass but were similar to white clover at 12 and 24 h after the start of fermentation. M. oleifera fermented faster than ryegrass or white clover. Hydrogen production from fermentation of M. oleifera might not have been diverted to methane production but removed by other compounds. In vitro fermentation showed differences in methane production across provenances. This suggests that it may be possible to select for low methane genotypes.
Keywords: 0701 Agriculture, Land and Farm Management